Measuring Health Professions Students’ Approaches toward Interprofessional Education - Hassan, Amel A.; Hamid, Amal M; Mohammed, Nadia Ahmed; Salih, Shahenda A. (Pakistan Journal of Medical & Health Sciences, 2022)
Background: efficient interprofessional learning acting a major part in preparing health professional undergraduates for future cooperative healthcare practice. Methods: To assess health professions students’ Approaches toward interprofessional education. A descriptive cross-sectional online survey was used among fourth-year undergraduate students in nursing, anaesthesia, and midwifery program (n=132), selected by purposive sampling technique. . The tool used for data collection was readiness interprofessional learning scale (RILS). Results: The majority of the students strongly agreed with the clients would substantially profit if healthcare undergraduates worked simultaneously (45.5%), communication skills would be educated with other healthcare learners (48.5%), and shared education will aid me to know my particular specialized limitations (53%), and for small-group learning to work, students need to respect and trust each other (62.1%). Conclusion: Interprofessional education is highly appreciated by all students with different disciplines.